A STUDY OF THE RELATIONSHIP BETWEEN TEACHERS’ PERCEPTION TOWARDS THEIR LEADERSHIP CAPACITY AND ORGANIZATIONAL COMMITMENT AT KAW DAI NATIONAL SCHOOL IN KARLI, SHAN STATE, MYANMAR - NAING, KYAW THET; YE, YAN (Scholar: Human Sciences, 2022)
This research study was to determine the relationship between teachers’ perception of their leadership capacity and organizational commitment at Kaw Dai National School in Karli, Shan State, Myanmar. The research instrument was a questionnaire adopted from Lamberts’ (2003) Leadership Capacity School Survey questionnaire and Ismail’s (2012) Survey Questionnaire for Organizational Commitment. The participants were all full-time teachers working in Kaw Dai National School in the academic year 2020 and the responses were analyzed utilizing Descriptive Statistic, Frequency and Percentage, Mean and Standard Deviation, and the Pearson Product-Moment Correlation Coefficient. Based on the study result, it was determined that there was a significant relationship between teachers’ perception towards their leadership capacity and their organization commitment at Kaw Dai National School. Additionally, the relationship was interpreted as moderate because the correlation (r)value was .624. Teachers’ quality, leadership capacity, and organizational commitment of teachers are important for student achievement and organizational success. But, at Kaw Dai National School, some aspects of teachers’ leadership capacity and organizational commitment were found to be still moderate, so, it was suggested that the school should consider improving them.